(untitled) (Research, Society and Development, 2021)
The objective was to analyze the preventive measures for mechanical ventilation associated pneumonia, as evidenced in the scientific literature. This is an integrative review study. For the elaboration of the research question, the PICO strategy was used. This research was done through online search in the databases of the Biblioteca Virtual em Saude (BVS) in the period from 2015 to 06/2020. After carefully reading the articles, 19 articles that met the inclusion criteria previously established were evaluated. This way, the following categories were defined after analysis for similarity of content: Category I- Preventive actions to face the PAV and Category II- Promotion of strategies to face the PAV. The study shows that the implementation of the bundle, proved to be an important tool that should be incorporated daily in care, reducing the risk of mechanical ventilation associated pneumonia, which becomes a resulted complication in hospitalized patients.